Hematological, Biochemical and Blood Lead Level Profile among Gasoline Exposed Station Workers in Sulaimaniya City - Mohammed, Sirwan M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2014)
Occupational exposure to toxic fumes of leaded gasoline has become a major public health concern. These fumes contain tremendous life threatening toxins, which can cause abnormal alterations in the functioning of many vital organs. The current study intended to find out any changes in the hematological and biochemical profile in correlation to the Blood lead levels among individuals occupationally exposed to gasoline and gasoline vapors as a fist line risk group. The mean Blood lead level among gasoline station workers (6.2±5µg/dL), was significantly higher (P=0.017) than controls (2.1 ± 6.4 µg/dL), and there was a significant (P=0.003) increase in Blood lead level (10.6±3.9 µg/dL) of smoking workers compared to non-smoking workers. The latter is above the permitted value for adult individuals. The workers had higher (P=0.01) concentration of hemoglobin (15.9 gm/dL), whereas, other hematological counts were within the normal limits. Serum alkaline phosphatase and uric acid were significantly higher among the workers (338±49.5 and 6.1±1.7) with P-value of (0.0001 and 0.038 respectively), whereas, no statistically significant differences were found among serum alanine transaminase, aspartate transaminase, creatinine, cholesterol and albumin.